ISLAM DAN KEBERAGAMAN (KEMAJEMUKAN) - Ade Dedi Rohayana (Jurnal Hukum Islam, 2011)
This article attempts to observe the significance and relevance of relation between Islam and pluralism. Historically, the idea of pluralism was adopted from the Prophet Muhammad PBUH when he lived in Madina. In this region, he lived in the heterogenic society together with different religions, races, colors, and tribes. There are some verses in the Qur’an and sayings of Prophet Muhammad for pluralism. From these verse and hadiths we can understand that Islam recognizes the pluralism. In doing so, we cannot deny that this thought become the important concepts of inclusivism’s implementation in Indonesia. Only these discussions are good advantages and positive sides for pluralism on behalf of Islam.